(untitled) (Revista Apotheke, 2024)
The aesthetic procedures and processes that shape artistic experiences are analysed in this article, based on the implementation of the non-formal art education project called Public Atelier. We present its action dynamics, evaluating the expanded application of its methods to formal pedagogical projects, going beyond the scope of art teaching. The reflection proposes an analysis of traditional teaching methodologies with the incorporation of aesthetic principles as a guiding form for the apprehension of varied content and the construction of new knowledge. With arguments based on the philosophically distinct conceptions of thinkers Friedrich Schiller (1759-1805) and John Dewey (1859-1952) about sensitive experience and its relationship with human formation, we will look for common ground to support our aim of contributing, together with our experience as art educators, with assumptions that legitimise education for sensitivity as a decisive factor in the integral formation of school subjects.